Evaluation of Inflammatory and Calcification after Implantation of Bioabsorbable Poly-L-Lactic Acid/Amorphous Calcium Phosphate Scaffolds in Porcine Coronary Arteries. (23rd January 2021) - Feng, Gaoke; Qin, Chaoshi; Sha, Fei; Lyu, Yongnan; Xia, Jinggang; Jiang, Xuejun
Abstract : Purpose . Our previous research has confirmed that the addition of nano-amorphous calcium phosphate (ACP) materials can improve the support of poly-L-lactic acid (PLLA) vascular scaffolds. Based on this, we continued to explore the effect of novel bioresorbable scaffold composed of PLLA and ACP nanoparticles on inflammation and calcification of surrounding tissues after scaffold implantation in porcine coronary artery. Methods . PLLA/ACP scaffolds in the experimental group and PLLA scaffolds in the control group were implanted into the coronary arteries of small pigs. Serum levels of C-reactive protein (CRP), calcium (Ca), and alkaline phosphatase (ALP) were measured before implantation and at 1, 6, 12, and 24 months after operation. Intravascular ultrasonography (IVUS) was performed to evaluate the vascular calcification score. The scaffold and surrounding tissues were hematoxylin-eosin staining for inflammation score. The scaffold and surrounding tissues were stained with NF- κ B and ALP, and the positive expression index was calculated. Western blot was used to detect the expression of IL-6 and BMP-2 in the tissues around the scaffold. Results . There was no statistically significant difference between the two groups in CRP, calcium, and ALP at preimplant, 1 month, 6 months, 12 months, and 24 months (P > 0.05 ). The inflammation score, NF- κ B positive expression index, and calcification score in the PLLA/ACP group were lower than that in the PLLA group at 12 months and 24 months (P < 0 05 ). The ALP positive expression index in the PLLA/ACP group was lower than that in the PLLA group at 6 months, 12 months, and 24 months (P < 0 05 ). Western blot results showed that the IL-6 expression level in the PLLA/ACP group was significantly lower than that in the control group at 6 months, 12 months, and 24 months (P < 0.05 ). The expression of BMP-2 in the PLLA/ACP group was significantly lower than that in the control group at 12 months and 24 months (P < 0.05 ). Conclusion . The PLLA/ACP composite scaffold has good biocompatibility. The incorporation of nanoscale ACP can reduce the inflammatory response caused by the acid metabolites of PLLA scaffolds, reduce the expression of procalcification factors in the body, and inhibit tissue calcification. The PLLA/ACP composite scaffold provides reliable guidance for the application and development of degradable vascular scaffold.